Mewujudkan Wisata Spiritual di Desa Adat Gelgel, Klungkung: Berbasis Website - I Made Mardika; Agus Kurniawan; I Putu Yudi Prabhadika; Ni Made Jaya Senastri (Postgraduated Community Service Journal, 2023)
Realizing Spiritual Tourism in the Gelgel Traditional Village Klungkung regency requires website-based tourism packaging and promotion. The aim is to empower the community in developing Spiritual Tourism through Information Technology. Three forms of activity are programmed, namely: creating tourist information, packaging content, and promoting spiritual tourism online. The solving method is carried out through: (1) Assistance in the preparation of temple cultural heritage information content as spiritual tourism on the website, (2) Assistance in structuring the potential of temple cultural heritage to be packaged into Spiritual tourist attractions, and (3) branding assistance and promoting "Gelgel as the Center for Spiritual and Classical Balinese Culture". The output is in the form of information on the cultural heritage of temples as spiritual tourism on the page https://warisanbudayabali.com/ Arrangement and packaging of cultural heritage as spiritual tourism, and online-based tourism promotion. Additional output is in the form of a monograph book on a spiritual tourism village model based on cultural heritage and simple copyrights.